Counterfeits of luxury branded products: what are the predictors and purchase intentions - Phau, Ian (School of Marketing, Curtin Business School, 2010)
This paper extends two related studies in counterfeiting by Tom et al. (1998) on consumer attitudes toward, and purchase history of counterfeit goods and Cordell et al. (1996) on investigating the extrinsic cues brand, price and retailer influencing consumption of counterfeits. The three main research questions are (a) to determine consumer's attitudes towards purchasing counterfeit products and whether these attitudes correlate with and predict past counterfeit consumption/non-consumption (b) to determine whether brand, price and retailer are determinants for consumers purchasing counterfeit products and (c) to identify the extent to which population segments consumed counterfeit products. Data collected from a mall intercept were analysed using various multivariate statistical techniques. The analysis has produced several important implications for manufacturers and policy makers for consideration.